Combined plant proteins as fishmeal replacements in pearlspot (Etroplus suratensis): Effects on growth performance, digestive enzymes and fatty acid composition - E. P. Madhubabu; R. Jannathulla; H. Imran Khan; Y. Mohamed Thoufeek; K. Ambasankar; J. Syama Dayal (Indian Journal of Fisheries, 2025)
A mix of plant proteins (PP) (soybean meal, groundnut oilcake, wheat gluten meal and corn gluten meal in a 4:2:2:2 ratio) was used to partially replace fishmeal in the diets of pearlspot (Etroplus suratensis). Five iso-nitrogenous diets (301.20-306.85 g kg-1 crude protein) were prepared by substituting fishmeal at 0% (control, FM-R0), 25% (FM-R25), 50% (FM-R50), 75% (FM-R75) and 100% (FM-R100). The results revealed that the growth performance remained optimal up to 50% fishmeal replacement, beyond which significant declines were observed. Digestive enzyme activities varied significantly (p